The RADial artery International ALliance (RADIAL) extended follow-up study: rationale and study protocol. (18th September 2019) - Gaudino, Mario; Benedetto, Umberto; Fremes, Stephen; Ballman, Karla; Biondi-Zoccai, Giuseppe; Sedrakyan, Art; Nasso, Giuseppe; Raman, Jai; Buxton, Brian; Hayward, Philip A; Moat, Neil; Collins, Peter; et al.
Abstract: It is generally accepted that radial artery (RA) grafts have better mid-term patency rate compared to saphenous vein grafts. However, the clinical correlates of the improved patency rate are still debated. Observational studies have suggested increased survival and event-free survival for patients who receive an RA rather than a saphenous vein, but they are open to bias and confounders. The only evidence based on randomized data is a pooled meta-analysis of 6 randomized controlled trial comparing the RA and the saphenous vein published by the RADial artery International Alliance (RADIAL). In the RADIAL database, improved freedom from follow-up cardiac events (death, myocardial infarction and repeat revascularization) was found at 5-year follow-up in the RA arm. The most important limitation of the RADIAL analysis is that most of the included trials had an angiographic follow-up in the first 5 years and it is unclear whether the rate of repeat revascularization (the main driver of the composite outcome) was clinically indicated due to per-protocol angiographies. Here, we present the protocol for the long-term analysis of the RADIAL database. By extending the follow-up beyond the 5th postoperative year (all trials except 1 did not have angiographic follow-up beyond 5 years), we aim to provide data on the role of RA in coronary artery bypass surgery with respect to long-term outcomes.